Νεοελληνική κριτική - Ζακυθηνός, Διονύσιος Α., 1905-1993; Παναγιωτόπουλος, Ι. Μ., 1901-1982; Παπανούτσος, Ευάγγελος Π., 1900-1982 (Βασική βιβλιοθήκη / Αετός ;, 1956)
Σούτσος, Παναγιώτης -- Ροΐδης, Εμμανουήλ -- Πολυλάς, Ιάκωβος -- Παλαμάς, Κωστής -- Ξενόπουλος, Γρηγόριος -- Συκούτρης, Ιωάννης κ.ά.